MAPEAMENTO E CARACTERIZAÇÃO DE CHERNOSSOLOS NO MUNICÍPIO DE TIMON-MA - OLIVEIRA, Deysiele Viana de (2022)
Knowledge about the soil is essential when its use is on the agenda, as this natural resource is used for a multitude of activities aimed at meeting human needs. However, the lack of knowledge about the productive potential and its aptitude is notorious, as losses caused by poor management and use are often noticed, especially when the soils are fertile. This research aimed to map and characterize the class of Chernosoils in the municipality of Timon (MA), soils of restricted occurrence and recently identified in the State of Maranhão. The methodology is based on the geosystemic approach, with methodological procedures based on literature review, field work, office and laboratory work. In the field, trenches were opened in toposequence and the soils were described according to the procedures of the Field Collection and Description Manual (2015) and the analyzes were performed according to criteria established by the Brazilian Soil Classification System (SANTOS et al, 2018). Thirteen undisturbed samples with a depth of 0-0.20 cm were also collected in order to understand the variability of soil attributes and their distribution in the analyzed area. The research allowed to verify the existence of the class of Haplic, Rendzic, Ebanic Chernosoils. The Chernosolos patch corresponds to 23.28 km² or 1.32% of the total area of the municipality of Timon. Small stain in relation to the others, however, its potential lies in its high fertility; proven in chemical analysis when presenting values > 65% of base saturation with a minimum V% value of 95.8%, maximum of 98.5% and a higher value for pH of 7.7. Exchangeable Ca contents are high, with an average of 18 cmol.dm-³, considering all profiles, which explains the absence of Al in the analyzed samples, indicating the low degree of weathering of the soils. Samples in toposequence showed great variability of attributes, o was counted by CV high and very high, with exchangeable K being the most heterogeneous variable and pH, with the least variation. Soils have high natural fertility, but low effective depth, with stony and rocky soils, which limits their potential for use. Local soils, if well managed, can guarantee significant production and expand local supply, guaranteeing work and income for the population.